The “Gentle Lie”: Women and the GDR Medical System in Film and Literature (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | Within the context of medical-historical research, this article compares the depiction of female patients in GDR and post-GDR fictional texts: Lothar Warneke’s Die Beunruhigung (1982), Christa Wolf’s Nachdenken über Christa T. (1968) and Leibhaftig (2002), and Kathrin Schmidt’s Du stirbst nicht (2009). This approach highlights the idiosyncrasies of GDR medicine, which demanded patients’ collaboration in therapeutic measures and hid from them the truth about their conditions. This custom, known as the “gentle lie,” as well as other top-down practices echo the state’s patriarchal attitude towards its citizens, particularly women, evidencing that the GDR claim of gender equality was not practiced in key areas of women’s lives. Furthermore, there is evidence that hierarchical structures denying patients’ agency persist today in eastern Germany. Résumé | Dans une perspective médico-historique, cet article compare la description de patientes dans des récits de fiction de la RDA et de l’ex-RDA: L’Inquiétude (Die Beunruhigung) de Lothar Warneke (1982), Christa T. (Nachdenken über Christa T.) (1968) et Le Corps même(Leibhaftig) de Christa Wolf (2002) ainsi que Tu ne vas pas mourir (Du stirbst nicht) de Kathrin Schmidt (2009). Cette approche met en lumière les idiosyncrasies de la médecine de la RDA, laquelle demandait la collaboration des patients dans les mesures thérapeutiques tout en leur cachant la vérité sur leur condition. Cette pratique—connue sous le nom de « doux mensonge »—ainsi que d’autres pratiques imposées d’en haut reflètent l’attitude patriarcale de l’État envers ses citoyens, et tout particulièrement envers les femmes, preuve que la revendication—faite par la RDA—de l’égalité des sexes n’était pas mise en œuvre dans des secteurs clés de la vie des femmes. En outre, tout porte à croire que les structures hiérarchiques privant les patients d’initiative continuent de se perpétuer aujourd’hui dans l’Est de l’Allemagne.